A educação em direitos humanos nas ações de extensão Universitária da Amazonia Amapaense - ANDRADE, Jemina de Araujo Moraes (Instituto Federal do Amapá, 2021)
This study mapped the Human Rights Education (EDH) under the focus of extension, in a university located in the north of the Brazilian Amazon. This research makes it possible not only to see the tendency of extension actions, but also to present the human rights education policy in dialogue with the new national guidelines for university extension, in order to awaken a culture in and for human rights. The problem raised was to question which extensionist tendencies in the EDH could highlight the dialogue between the university and the socially vulnerable groups. The outline was directed to two categories: a) gender, women and LGBT population; b) Racial, ethnic and identity groups. The study revealed the existence of human rights education in registered extension projects, especially regarding women and indigenous people, but with gaps and extension modalities that should be encouraged as an institutional policy.